Marquês de Pombal e a baixa de Lisboa. Poder, influência e cultura na nova baixa - Guilherme Monteiro Belo dos Santos (2017)
For a long time we have been trying to decipher what the construction of Lisbon's Downtown was based on to have acquired the characteristics that we can still witness today. The reticulated and well-organized form of a city created in the eighteenth century raises several questions. There are several theories about which movement has taken control of the fabric of the city of Lisbon - one of them, Freemasonry, becomes the protagonist of several works, that try to invoke its symbology, both in the life of Sebastião José de Carvalho e Melo, as in the city itself. For this theory, its veracity will hardly be proved, although it is quite enticing. There is, however, a movement that could easily be involved, taking into account the year it reached its apogee as well as the ideological relationship coinciding with the shape of the new city - the Enlightenment. It is within this movement that all the conditions, legislation and minds of that time, which portuguese history has been developing, meet and create, within its bosom, a work and style, truly portuguese and Enlightened.